Cryptocurrency Estate Planning: The Challenges, Suggested Solutions and Malaysia’s Future Directions - Katuk, Norliza; Abd Wahab, Norazlina; Kamis, Nur Syaedah (Emerald Publishing Limited, 2023)
This paper aims to collect evidence on the issues and challenges in cryptocurrency estate planning and the possible approaches or methods to address them. Then, this paper also aims to understand Malaysia’s situation compared to global situations and determine how the country could address those challenges. Design/methodology/approach This study adapted a standard systematic review protocol named preferred reporting items for systematic reviews and meta-analyses, guided by three research questions: what are the challenges of cryptocurrency estate planning, how do researchers and practitioners address the issues or challenges and how could Malaysians move towards sustainable cryptocurrency estate planning? Relevant documents reported on cryptocurrency estate planning were analysed using thematic analysis. Findings The results of this review suggested that the issues and challenges in cryptocurrency estate planning can be described from six aspects: awareness, financial aspects, law, process, security and taxation. On the other hand, the approaches or methods to address these challenges may be categorised into laws, processes and technology. Further, a framework for cryptocurrency estate planning in Malaysia is proposed as an initial step towards a sustainable economy and society in Malaysia. Research limitations/implications The state and the use of cryptocurrency are still considered new in most countries globally. Hence, people are yet to be aware of the issues that may arise from it. Nevertheless, cryptocurrency estate planning will soon become an area of interest in which this study could enhance the literature and contribute knowledge to understanding the situation. Originality/value This study collected evidence on the issues and the approaches to address cryptocurrency estate planning. This study then focused on the Malaysian perspective by proposing a framework that was not covered by existing studies